In Vitro Caco-2 Cell Permeability Studies of Ziprasidone Hydrochloride Monohydrate Nanocrystals - KARAKÜÇÜK, Alptuğ (Turk J Pharm Sci, 2021)
OBJECTIVES: The current study focused on the evaluation of the cytotoxic effect and permeability of ziprasidone hydrochloride monohydrate (ZHM) nanocrystals on Caco-2 cells. MATERIALS AND METHODS: ZHM nanocrystals were prepared by the microfluidization method in the presence of polyvinylpyrrolidone as a stabilizer. Particle size (PS), particle size distribution (PDI), and zeta potential (ZP) values were measured in characterization studies. In vitro cytotoxic effects of ZHM nanocrystals were investigated using the 3-(4,5-dimetylthiazol-2-yl)-2,5-diphenyltetrazolium bromide test. Caco-2 transport studies were conducted with formulations of ZHM coarse powder and nanocrystals. RESULTS: Nanocrystals were obtained with 400-600 nm PS, 0.1-0.4 PDI, and >20 mV ZP values. The cell viability remained 100% for all sample groups. The permeability value of ZHM nanocrystals through Caco-2 cells increased 2.3-fold in comparison with ZHM coarse powder. Cumulative drug transport also increased at the end of the sampling period. CONCLUSION: Nanocrystal technology helps to increase the permeability of drug particles by increasing the saturation solubility.